Preparation and application of selectively phosphorized two-dimensional heterojunction photocatalyst

By mixing ultra-thin graphite phase carbon nitride powder with tungsten selenide nanosheets and phosphating treatment, a two-dimensional heterojunction catalyst of tungsten selenide-carbon nitride was prepared, which solved the serious problem of photogenerated carrier recombination of a single component carbon nitride catalyst material, and achieved efficient solar hydrogen production.

CN119680615APending Publication Date: 2025-03-25SHAANXI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510118830.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The single-component carbon nitride catalyst material has severe photocarrier recombination, resulting in low energy-quality transmission efficiency of solar hydrogen production.

Method used

Tungsten selenide-carbon nitride two-dimensional heterojunction catalyst was prepared by mixing ultra-thin graphite phase carbon nitride powder with tungsten selenide nanosheets and phosphating treatment. This method improves the separation efficiency of photogenerated carriers by closely contacting the interface through the cross-band arrangement and close contact.

Benefits of technology

The photocatalytic performance has been significantly improved. Compared with pure graphite phase carbon nitride, the photocatalytic activity has been increased by nearly 5 times, and the hydrogen production rate has also been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680615A_ABST
    Figure CN119680615A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of green hydrogen energy preparation, in particular to preparation of a selectively phosphorized two-dimensional heterojunction photocatalyst, which comprises the following steps: step 1, preparing ultrathin graphite phase carbon nitride powder by using melamine as a raw material; preparing tungsten selenide nanosheets by taking tungsten selenide powder and sodium hydroxide nanosheets as raw materials; and 2, mixing the ultrathin graphite phase carbon nitride powder and the tungsten selenide nanosheets, and carrying out phosphating treatment in combination with sodium hypophosphite to prepare the tungsten selenide-carbon nitride two-dimensional heterojunction catalyst. When the tungsten selenide nanosheet is combined to a carbon nitride semiconductor through annealing, due to cross-band arrangement of tungsten selenide and carbon nitride, electrons on a carbon nitride conduction band can be rapidly transferred to a tungsten selenide conduction band, and water is reduced into hydrogen. Meanwhile, holes can also be migrated to a valence band of tungsten selenide and consumed by triethanolamine. Due to tight and abundant contact of the interface, charge transfer at the heterogeneous interface is accelerated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of green hydrogen energy preparation, and in particular to the preparation and application of a selectively phosphated two-dimensional heterojunction photocatalyst. Background Art

[0002] The energy needed for the current development of human society is mainly traditional fossil energy such as coal, oil, and natural gas. The process of energy utilization has caused serious carbon emissions and air pollution problems, and fossil energy is non-renewable. In order to achieve high-quality social development with carbon peak and carbon neutrality, clean and renewable energy must be developed and utilized. Studies have found that the reserves of solar energy are very rich, which is of great significance to human economic and social development and ecological and environmental balance. However, the development and utilization of solar energy has problems such as uneven distribution in four seasons and day and night, and low energy density. Hydrogen energy is a renewable chemical energy with high energy density, zero carbon emissions, and convenient storage and transportation. Therefore, hydrogen energy is considered to be an ideal energy source for the future and has important strategic significance in the future supply of clean and renewable energy. Based on this, converting solar energy into hydrogen energy for storage and utilization can effectively solve the energy supply and environmental pollution problems faced by human social development, and provide a strong energy driving force for national energy supply security, economic and social development, etc.

[0003] Solar water splitting hydrogen production technology based on semiconductor photocatalytic materials is a green and environmentally friendly hydrogen production method. The key lies in the development and preparation of efficient, stable and low-cost solar hydrogen production photocatalysts. The basic principle of this technology is that sunlight irradiates the semiconductor catalyst to stimulate the generation of electron-hole pairs, and the generated photogenerated carriers separate and migrate to the active sites on the catalyst surface for redox reactions to produce hydrogen and oxygen, thereby realizing the conversion and storage of solar energy → hydrogen energy.

[0004] At present, a large number of semiconductor materials have been used for solar photocatalytic decomposition of water to produce hydrogen. Graphite phase carbon nitride is a metal-free polymer semiconductor material with a band gap of about 2.6eV. Its electronic structure meets the potential for photocatalytic hydrogen production and is widely used in solar photocatalytic hydrogen production research. However, the single-component carbon nitride catalyst material has serious photogenerated carrier recombination, which greatly reduces its energy-to-mass transmission efficiency for solar hydrogen production. Summary of the invention

[0005] In view of the problem that the single-component carbon nitride catalyst material in the prior art limits the energy transfer efficiency of solar hydrogen production due to severe photogenerated carrier recombination, the present invention provides the preparation and application of a selectively phosphated two-dimensional heterojunction photocatalyst.

[0006] The present invention is achieved through the following technical solutions: A preparation method of a selectively phosphated two-dimensional heterojunction photocatalyst comprises the following steps: Step 1, preparing ultra-thin graphite phase carbon nitride powder using melamine as raw material; Tungsten selenide nanosheets were prepared using tungsten selenide powder and sodium hydroxide nanosheets as raw materials; Step 2, mixing ultra-thin graphite phase carbon nitride powder and tungsten selenide nanosheets, and combining with sodium hypophosphite to prepare a tungsten selenide-carbon nitride two-dimensional heterojunction catalyst through phosphating.

[0007] Preferably, in step 1, the preparation steps of ultra-thin graphite phase carbon nitride powder are: Step 101, heat-treating melamine at room temperature to obtain light yellow carbon nitride; Step 102, grinding the carbon nitride into powder, performing annealing treatment, cooling to room temperature, and then grinding to obtain ultra-thin graphite phase carbon nitride powder.

[0008] Preferably, in step 101, during the heat treatment, the heating rate is 5°C / min, the temperature is 500-520°C, and the time is 4-5h.

[0009] Preferably, in step 102, during the annealing treatment, the temperature is 800-820°C and the time is 10-15 minutes.

[0010] Preferably, in step 1, the preparation steps of tungsten selenide nanosheets are: adding tungsten selenide powder and sodium hydroxide nanosheets to an ethanol solution in a ratio of (1:1) to (1:2), stirring at room temperature, then performing a hydrothermal reaction, then naturally cooling to room temperature, collecting the precipitate after centrifugal washing, and then drying to obtain tungsten selenide nanosheets.

[0011] Preferably, during the hydrothermal reaction, the temperature is 180-200° C. and the time is 10-12 h.

[0012] Preferably, during drying, the temperature is 60-80° C. and the time is 10-18 hours.

[0013] Preferably, in step 2, the specific steps of preparing the tungsten selenide-carbon nitride two-dimensional heterojunction catalyst are: Step 201, mixing, stirring and grinding tungsten selenide nanosheets and ultrathin graphite phase carbon nitride powder in a ratio of (1:50) to (15:50) to obtain a phosphated sample, and then putting the sample into a porcelain boat, and placing the porcelain boat at the lower air outlet of a tube furnace; Sodium hypophosphite is added into a porcelain boat, and the porcelain boat is placed at the upwind side of a tube furnace; wherein the ratio of sodium hypophosphite to the sample to be phosphated is (8:1) to (10:1); Step 202, connect the two ends of the tubular furnace quartz tube to the argon gas cylinder and the exhaust port, and exhaust in advance, then heat up to 200-220°C at 5°C / min, stop heating after phosphating for 2-4 hours, close the gas cylinder after the tubular furnace naturally cools to room temperature, open the tubular furnace, collect the powder sample, and grind it to obtain the phosphated tungsten selenide-carbon nitride two-dimensional heterojunction catalyst.

[0014] A product obtained by preparing a selectively phosphated two-dimensional heterojunction photocatalyst.

[0015] The invention discloses an application of a photocatalyst in the field of hydrogen production.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a selectively phosphated two-dimensional heterojunction photocatalyst. The preparation method combines ultrathin graphite phase carbon nitride powder and tungsten selenide nanosheets, and then undergoes a phosphating treatment to successfully prepare a tungsten selenide-carbon nitride two-dimensional heterojunction catalyst. The tungsten selenide nanosheets are bonded to the carbon nitride semiconductor by annealing. Due to the cross-band arrangement of tungsten selenide and carbon nitride, the electrons on the carbon nitride conduction band can be quickly transferred to the tungsten selenide conduction band, and water is reduced to hydrogen. At the same time, holes can also migrate to the valence band of tungsten selenide and be consumed by triethanolamine. Due to the close and abundant contact of the interface, the charge transfer at the heterogeneous interface is accelerated.

[0017] The heterojunction catalyst material of the present invention has the following advantages: First, after the composite tungsten selenide nanosheets are treated with phosphating, phosphorus will be selectively doped into the tungsten selenide, with obvious doping selectivity.

[0018] Second, the tungsten selenide nanosheets and graphite phase carbon nitride heterojunction materials have a 2D / 2D two-dimensional surface-to-surface contact mode, with close interface contact and large contact interface, which is conducive to the transmission and separation of interfacial charges.

[0019] Third, tungsten selenide has the ability to extract electrons and provide abundant catalytic active sites during the catalytic reaction, which promotes the separation of carbon nitride charges and the mass transfer of catalytic reactions. The activity is further improved after phosphating. The photocatalytic activity is nearly 5 times higher than that of pure graphite phase carbon nitride. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a flow chart of the preparation of a selectively phosphated two-dimensional heterojunction photocatalyst of the present invention; Figure 2 is the XRD pattern of the ultra-thin layer carbon nitride, tungsten selenide-carbon nitride and phosphated tungsten selenide-carbon nitride in Example 1; Figure 3 is a TEM image of the ultra-thin layer of carbon nitride in Example 1; Figure 4is a TEM image of tungsten selenide carbon nitride in Example 1; Figure 5 is a TEM image of tungsten selenide phosphide carbon nitride in Example 1; Figure 6 is a spherical aberration electron microscope image of tungsten selenide phosphide carbon nitride in Example 1; Figure 7 is the element distribution image of tungsten selenide phosphide carbon nitride in Example 1; Figure 8 is the light absorption diagram of ultra-thin layer carbon nitride, tungsten selenide-carbon nitride and phosphated tungsten selenide-carbon nitride obtained in Example 1; Fig. 9 The fluorescence spectra of ultra-thin carbon nitride, tungsten selenide-carbon nitride and phosphated tungsten selenide-carbon nitride obtained in Example 1 are shown in FIG. Fig.10 It is a hydrogen production activity diagram of ultra-thin carbon nitride, tungsten selenide-carbon nitride and the phosphated tungsten selenide-carbon nitride obtained in Example 1; Fig.11 is a graph of hydrogen production rates of ultra-thin carbon nitride, tungsten selenide-carbon nitride, and the phosphated tungsten selenide-carbon nitride obtained in Example 1; Fig.12 This is the test result of the stability of the photocatalytic hydrogen production activity of the phosphated tungsten selenide-carbon nitride obtained in Example 1. DETAILED DESCRIPTION

[0021] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0022] The present invention discloses a method for preparing a selectively phosphated two-dimensional heterojunction photocatalyst. Figure 1 , including the following steps: Step 1, preparing ultra-thin graphite phase carbon nitride powder using melamine as raw material, specifically: Step 101, heat-treating melamine at room temperature at a heating rate of 5°C / min to obtain light yellow carbon nitride; during the heat treatment, the heating rate is 5°C / min, the temperature is 500-520°C, and the time is 4-5h.

[0023] Step 102, grinding the carbon nitride into powder, annealing at 800-820°C for 10-15 minutes, cooling to room temperature, and grinding to obtain ultra-thin graphite phase carbon nitride powder.

[0024] Tungsten selenide nanosheets are prepared using tungsten selenide powder and sodium hydroxide nanosheets as raw materials. Specifically, tungsten selenide powder and sodium hydroxide nanosheets are added to an ethanol solution in a ratio of (1:1) to (1:2), stirred at room temperature, and then subjected to a hydrothermal reaction. The solution is then naturally cooled to room temperature, and the precipitate is collected after centrifugal washing, and then dried to obtain tungsten selenide nanosheets. During the hydrothermal reaction, the temperature is 180-200°C and the time is 10-12h. During the drying, the temperature is 60-80°C and the time is 10-18h.

[0025] Step 2, mixing ultra-thin graphite phase carbon nitride powder and tungsten selenide nanosheets, and preparing tungsten selenide-carbon nitride two-dimensional heterojunction catalyst by phosphating with sodium hypophosphite, the specific steps are: Step 201, mixing, stirring and grinding tungsten selenide nanosheets and ultrathin graphite phase carbon nitride powder in a ratio of (1:50) to (15:50) to obtain a phosphated sample, and then putting the sample into a porcelain boat, and placing the porcelain boat at the lower air outlet of a tube furnace; Sodium hypophosphite is added into a porcelain boat, and the porcelain boat is placed at the upwind side of a tube furnace; wherein the ratio of sodium hypophosphite to the sample to be phosphated is (8:1) to (10:1); Step 202, connect the two ends of the tubular furnace quartz tube to the argon gas cylinder and the exhaust port, and exhaust in advance, then heat up to 200-220°C at 5°C / min, stop heating after phosphating for 2-4 hours, close the gas cylinder after the tubular furnace naturally cools to room temperature, open the tubular furnace, collect the powder sample, and grind it to obtain the phosphated tungsten selenide-carbon nitride two-dimensional heterojunction catalyst.

[0026] In the preparation of a selectively phosphated two-dimensional heterojunction photocatalyst of the present invention, when a tungsten selenide nanosheet is bonded to a carbon nitride semiconductor by annealing, due to the cross-band arrangement of tungsten selenide and carbon nitride, the electrons on the carbon nitride conduction band can be quickly transferred to the tungsten selenide conduction band and reduce water to hydrogen. At the same time, holes can also migrate to the valence band of tungsten selenide and be consumed by triethanolamine. Due to the close and abundant contact of the interface, the charge transfer at the heterogeneous interface is accelerated.

[0027] Specifically, the present application uses selective phosphating treatment to broaden the light absorption range of the tungsten selenide-carbon nitride two-dimensional heterojunction catalyst, improve the separation efficiency of photogenerated electron-hole pairs, and thus significantly enhance its photocatalytic performance. Among them, the phosphating treatment not only improves the surface structure of the catalyst, but also improves its chemical stability, so that the catalyst can maintain a high activity in a long-term photocatalytic reaction and prolongs its service life. The obtained photocatalyst can be applied to multiple fields such as hydrogen production, environmental purification, and organic synthesis. Especially in the field of hydrogen production, it is expected to become an efficient and environmentally friendly new hydrogen production material.

[0028] The invention also discloses a photocatalyst obtained by preparing a selectively phosphated two-dimensional heterojunction photocatalyst.

[0029] The present invention also discloses an application of a photocatalyst in the field of hydrogen production. The conditions for hydrogen production are: 0.05 g catalyst, photo-deposited platinum (3 wt%), 50 mL reaction solution, 300 W Xe lamp (λ≥420 nm) as light source, 10% triethanolamine (3 mL) as sacrificial agent, and the test is stopped after 4 hours of reaction each time, and nitrogen is purged for 15 minutes to remove the generated hydrogen in the reaction system, and then the visible light photocatalytic hydrogen production test is continued for four cycles.

[0030] The specific process of preparing a selectively phosphated two-dimensional heterojunction photocatalyst of the present invention is as follows: Step 1: At room temperature, weigh 10 g of melamine and put it into a 50 mL crucible. Cover the crucible with a lid and transfer it to a muffle furnace. Heat it at 5°C / min to 520°C for 4 h to obtain light yellow carbon nitride, which is then ground into powder.

[0031] The temperature of the muffle furnace was set at 800°C, 10 g of light yellow carbon nitride powder was weighed and put into the 50 mL crucible again, and the crucible was covered. The crucible was quickly placed in the muffle furnace for rapid annealing for 10 min, and then the muffle furnace was opened and the crucible was quickly taken out. After cooling to room temperature, the ultrathin graphite phase carbon nitride powder was ground.

[0032] Weigh 30 mg of tungsten selenide powder and 45 mg of sodium hydroxide nanosheets, add them to 60 mL of 95% ethanol solution, stir at room temperature for 30 min, transfer to a polytetrafluoroethylene liner, take out the stirrer, tighten the stainless steel high-pressure reactor, and place it in an oven for hydrothermal reaction at 180 ° C for 12 h. Then open the oven, wait until it cools naturally to room temperature, open the reactor, centrifuge and wash with deionized water for more than 3 times, collect the precipitate and dry it in a vacuum oven at 60 ° C for 12 h to obtain the desired tungsten selenide nanosheets.

[0033] Step 2: weigh 1-15 mg of tungsten selenide nanosheets and 50 mg of ultrathin graphite phase carbon nitride powder, mix them thoroughly, stir and grind them for 60 minutes, then put them into a rectangular porcelain boat, and then place the porcelain boat at the downwind port of the tube furnace.

[0034] Weigh 450 mg of sodium hypophosphite and add it to a porcelain boat, and then place the porcelain boat at the upwind side of the tube furnace.

[0035] Connect the two ends of the tubular furnace quartz tube to the argon gas cylinder and the exhaust port, exhaust in advance at a ventilation rate of 100 ppm for 30 minutes, then set the temperature and increase the temperature to 200°C at 5°C / min. Stop heating after phosphating for 2 hours. After the tubular furnace naturally cools to room temperature, close the gas cylinder, open the tubular furnace, collect the powder sample, and grind it to obtain the phosphated tungsten selenide-carbon nitride two-dimensional heterojunction catalyst.

[0036] Step 3, hydrogen production experiment: Weigh 50 mg of the obtained catalyst sample and add it to 27 mL of deionized water, transfer it to a 50 mL hydrogen production reactor, measure 3 mL of triethanolamine liquid as a hole sacrificial agent with a measuring cylinder and add it to the above reactor, stir it with a magnetic bar for 10 minutes, and add 10 μL of chloroplatinic acid aqueous solution (H2PtCl6·6H2O, 0.7 mg / mL) again. After nitrogen bubbling for 20 minutes, turn on the magnetic stirrer and xenon light source, and carry out hydrogen production reaction under light.

[0037] The photocatalytic activity of the phosphated tungsten selenide-carbon nitride two-dimensional heterojunction catalyst is nearly 5 times higher than that of pure graphite phase carbon nitride, reaching 688umol / (g·h).

[0038] Example 1 Step 1: At room temperature, weigh 10 g of melamine and put it into a 50 mL crucible. Cover the crucible with a lid and transfer it to a muffle furnace. Heat the crucible at 5 °C / min to 520 °C for 4 h to obtain light yellow carbon nitride, which is then ground into powder.

[0039] The temperature of the muffle furnace was set at 800°C, 10 g of light yellow carbon nitride powder was weighed and put into the 50 mL crucible again, and the crucible was covered. The crucible was quickly placed in the muffle furnace for rapid annealing for 10 min, and then the muffle furnace was opened and the crucible was quickly taken out. After cooling to room temperature, the ultrathin graphite phase carbon nitride powder was ground.

[0040] Weigh 30 mg of purchased tungsten selenide powder and 45 mg of sodium hydroxide nanosheets, add them to 60 mL of ethanol solution, stir at room temperature for 30 min, transfer to a polytetrafluoroethylene liner, take out the stirrer, tighten the stainless steel high-pressure reactor, and place it in an oven for hydrothermal reaction at 180°C for 12 h. Then open the oven, wait until it cools naturally to room temperature, open the reactor, wash it with deionized water for more than 3 times, collect the precipitate and dry it in a 60°C vacuum oven for 12 h to obtain the desired tungsten selenide nanosheets.

[0041] Step 2: weigh 5 mg of tungsten selenide nanosheets and 50 mg of ultrathin graphite phase carbon nitride powder, mix them thoroughly, stir and grind them for 60 minutes, then put them into a rectangular porcelain boat, and then place the porcelain boat at the downwind of the tube furnace.

[0042] Weigh 450 mg of sodium hypophosphite and add it to a porcelain boat, and then place the porcelain boat at the upwind side of the tube furnace.

[0043] Connect the two ends of the tubular furnace quartz tube to the argon gas cylinder and the exhaust port, exhaust in advance at a ventilation rate of 100 ppm for 30 minutes, then set the temperature and increase the temperature to 200°C at 5°C / min. Stop heating after phosphating for 2 hours. After the tubular furnace naturally cools to room temperature, close the gas cylinder, open the tubular furnace, collect the powder sample, and grind it to obtain the phosphated tungsten selenide-carbon nitride two-dimensional heterojunction catalyst.

[0044] Weigh 50 mg of the catalyst sample obtained in Example 1 and add it to 27 mL of deionized water, then transfer it to a 50 mL hydrogen production reactor. Measure 3 mL of triethanolamine liquid as a hole sacrificial agent with a measuring cylinder and add it to the reactor. Stir it with a magnetic stirrer for 10 min, and then add 10 μL of chloroplatinic acid aqueous solution (H2PtCl6·6H2O, 0.7 mg / mL). After bubbling with nitrogen for 20 min, turn on the magnetic stirrer and xenon light source to carry out hydrogen production reaction under illumination.

[0045] The photocatalytic activity of the catalyst in this example is 4.25 times higher than that of pure graphite carbon nitride, reaching 688 umol / (g·h).

[0046] Reference Figure 2 The phosphated tungsten selenide-carbon nitride catalyst produced diffraction intensities at 2θ=13.66° and 31.56°, which correspond to the (002) and (100) crystal planes of tungsten selenide (PDF:01-089-5257), while the diffraction intensity at 2θ=27.3° was attributed to the (002) crystal plane of carbon nitride, indicating that tungsten selenide and carbon nitride formed a compact heterostructure after high-temperature calcination.

[0047] Reference Figure 3 , the TEM image of carbon nitride shows its lamellar structure, indicating that carbon nitride nanosheets were successfully synthesized in the present application.

[0048] Reference Figure 4 , the TEM image of tungsten selenide-carbon nitride shows the presence of tungsten selenide in the carbon nitride lamellar structure, indicating that tungsten selenide and carbon nitride form a compact heterostructure after high temperature treatment in the present application.

[0049] Reference Figure 5 , the TEM image of the phosphated tungsten selenide-carbon nitride shows the presence of tungsten selenide in the carbon nitride lamellar structure, indicating that tungsten selenide and carbon nitride form a compact heterostructure after high temperature treatment in the present application.

[0050] Reference Figure 6The spherical aberration image of the phosphated tungsten selenide-carbon nitride shows the presence of tungsten selenide in the carbon nitride layer structure, indicating that tungsten selenide and carbon nitride form a compact heterostructure after high temperature treatment in this application.

[0051] Reference Figure 7 , the spatial distribution of tungsten selenide and carbon nitride in the 2D / 2D heterostructure was determined by EDX element distribution analysis. It can be seen that the C and N elements are evenly distributed throughout the composite material, while the W and Se elements are mainly distributed in some layered structures on the surface of carbon nitride, which indicates that the phosphated tungsten selenide-carbon nitride catalyst is a heterostructure formed with 2D carbon nitride as a substrate and 2D tungsten selenide. It was observed that the distribution of phosphorus elements is mainly concentrated on 2D tungsten selenide, which indicates that the selectively phosphated tungsten selenide-carbon nitride with heterostructure was successfully prepared.

[0052] Example 2 Step 1: At room temperature, weigh 10 g of melamine and put it into a 50 mL crucible. Cover the crucible with a lid and transfer it to a muffle furnace. Heat it at 5 °C / min to 520 °C for 4 h to obtain light yellow carbon nitride, which is then ground into powder. The temperature of the muffle furnace was set at 800°C, 10 g of light yellow carbon nitride powder was weighed and put into the 50 mL crucible again, and the crucible was covered. The crucible was quickly placed in the muffle furnace for rapid annealing for 10 min, and then the muffle furnace was opened and the crucible was quickly taken out. After cooling to room temperature, the ultrathin graphite phase carbon nitride powder was ground.

[0053] Weigh 30 mg of purchased tungsten selenide powder and 45 mg of sodium hydroxide nanosheets, add them to 60 mL of ethanol solution, stir at room temperature for 30 min, transfer to a polytetrafluoroethylene liner, take out the stirrer, tighten the stainless steel high-pressure reactor, and place it in an oven for hydrothermal reaction at 180°C for 12 h. Then open the oven, wait until it cools naturally to room temperature, open the reactor, wash it with deionized water for more than 3 times, collect the precipitate and dry it in a 60°C vacuum oven for 12 h to obtain the desired tungsten selenide nanosheets.

[0054] Step 2: weigh 10 mg of tungsten selenide nanosheets and 50 mg of ultrathin graphite phase carbon nitride powder, mix them thoroughly, stir and grind them for 60 minutes, then put them into a rectangular porcelain boat, and then place the porcelain boat at the downwind port of the tube furnace.

[0055] Weigh 450 mg of sodium hypophosphite and add it to a porcelain boat, and then place the porcelain boat at the upwind side of the tube furnace.

[0056] Connect the two ends of the tubular furnace quartz tube to the argon gas cylinder and the exhaust port, exhaust in advance at a ventilation rate of 100 ppm for 30 minutes, then set the temperature and increase the temperature to 200°C at 5°C / min. Stop heating after phosphating for 2 hours. After the tubular furnace naturally cools to room temperature, close the gas cylinder, open the tubular furnace, collect the powder sample, and grind it to obtain the phosphated tungsten selenide-carbon nitride two-dimensional heterojunction catalyst.

[0057] Weigh 50 mg of the catalyst sample obtained in Example 2 and add it to 27 mL of deionized water, transfer it to a 50 mL hydrogen production reactor, measure 3 mL of triethanolamine liquid as a hole sacrificial agent with a measuring cylinder and add it to the above reactor, stir it with a magnetic bar for 10 min, and add 10 μL of chloroplatinic acid aqueous solution (H2PtCl6·6H2O, 0.7 mg / mL) again. After nitrogen bubbling and purging for 20 min, turn on the magnetic stirrer and xenon lamp light source, and carry out hydrogen production reaction under light.

[0058] The photocatalytic activity of the catalyst in this example is nearly 2.87 times higher than that of pure graphite phase carbon nitride, reaching 465umol / (g·h).

[0059] Comparative Example 1 Step 1: At room temperature, weigh 10 g of melamine and put it into a 50 mL crucible. Cover the crucible with a lid and transfer it to a muffle furnace. Heat it at 5 °C / min to 520 °C for 4 h to obtain light yellow carbon nitride, which is then ground into powder. Step 2: Set the temperature of the muffle furnace to 800°C, weigh 10g of light yellow carbon nitride powder and put it into the 50mL crucible again, cover the crucible, quickly put the crucible into the muffle furnace for rapid annealing for 10 minutes, then open the muffle furnace and quickly take out the crucible, cool to room temperature and grind to obtain ultra-thin graphite phase carbon nitride powder.

[0060] Comparative Example 2 Step 1: Weigh 30 mg of purchased tungsten selenide powder and 45 mg of sodium hydroxide nanosheets, add them to 60 mL of ethanol solution, stir at room temperature for 30 minutes, transfer to a polytetrafluoroethylene liner, take out the stirrer, tighten the stainless steel high-pressure reactor, and place it in an oven for hydrothermal reaction at 180°C for 12 hours. Then open the oven, wait until it cools naturally to room temperature, open the reactor, centrifuge and wash with deionized water for more than 3 times, collect the precipitate and dry it in a 60°C vacuum oven for 12 hours to obtain the desired tungsten selenide nanosheets.

[0061] Step 2: Weigh 1-15 mg of tungsten selenide nanosheets and 50 mg of ultra-thin graphite phase carbon nitride powder, mix and grind them for 60 minutes, then put them into a rectangular magnetic boat, and then place the magnetic boat at the lower air outlet of the tube furnace.

[0062] Step 3: Connect the two ends of the tubular furnace quartz tube to the argon gas cylinder and the exhaust port, exhaust in advance at a ventilation rate of 100 ppm for 30 minutes, then set the temperature, and increase the temperature to 200 °C at 5 °C / min. Stop heating after heating for 2 hours. After the tubular furnace naturally cools to room temperature, close the gas cylinder, open the tubular furnace, collect the powder sample, and grind it to obtain a tungsten selenide-carbon nitride two-dimensional heterojunction catalyst.

[0063] Reference Figure 8 Compared with pure graphite phase carbon nitride, the visible light absorption edge of the phosphated tungsten selenide-carbon nitride two-dimensional heterojunction catalyst is broadened and its light absorption range is increased, which is conducive to absorbing light for photocatalytic hydrogen production. Reference Fig. 9 Analysis of the fluorescence spectra of carbon nitride, tungsten selenide-carbon nitride and phosphated tungsten selenide-carbon nitride shows that the minimum radiative recombination quenching signal of photogenerated electrons and holes in the phosphated tungsten selenide-carbon nitride two-dimensional heterojunction catalyst is lower than that in pure graphite phase carbon nitride, indicating that its carrier recombination is suppressed. Reference Fig.10 , the hydrogen production activity diagrams of ultra-thin carbon nitride, tungsten selenide-carbon nitride and phosphated tungsten selenide-carbon nitride were analyzed. It was found that under visible light irradiation (k>420 nm), the hydrogen evolution rate of carbon nitride was low, while the hydrogen evolution rate of tungsten selenide-carbon nitride catalyst with 2D / 2D heterostructure was significantly higher than that of ultra-thin carbon nitride, and the phosphated tungsten selenide-carbon nitride catalyst had the highest hydrogen production rate.

[0064] Reference Fig.11 , the hydrogen production rate diagrams of ultra-thin carbon nitride, tungsten selenide-carbon nitride and phosphated tungsten selenide-carbon nitride were analyzed, and it was found that the hydrogen production rate of ultra-thin carbon nitride catalyst was 162 umol / (g·h), and the hydrogen production rate of phosphated tungsten selenide-carbon nitride catalyst was 688 umol / (g·h), which was 4.25 times that of ultra-thin carbon nitride.

[0065] Reference Fig.12 ,Analysis of the hydrogen production stability of phosphated tungsten selenide-carbon nitride shows that after four cycles, the hydrogen production activity of the phosphated tungsten selenide-carbon nitride catalyst is still relatively stable and has not decreased significantly.

[0066] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. Preparation of a selectively phosphated two-dimensional heterojunction photocatalyst, characterized in that: The following steps are involved: Step 1, preparing ultra-thin graphite phase carbon nitride powder using melamine as raw material; Tungsten selenide nanosheets were prepared using tungsten selenide powder and sodium hydroxide nanosheets as raw materials; Step 2, mixing ultra-thin graphite phase carbon nitride powder and tungsten selenide nanosheets, and combining with sodium hypophosphite to prepare a tungsten selenide-carbon nitride two-dimensional heterojunction catalyst through phosphating.

2. The preparation of the selectively phosphated two-dimensional heterojunction photocatalyst according to claim 1, characterized in that: In step 1, the preparation steps of ultra-thin graphite phase carbon nitride powder are: Step 101, heat-treating melamine at room temperature to obtain light yellow carbon nitride; Step 102, grinding the carbon nitride into powder, performing annealing treatment, cooling to room temperature, and then grinding to obtain ultra-thin graphite phase carbon nitride powder.

3. The preparation of the selectively phosphated two-dimensional heterojunction photocatalyst according to claim 2, characterized in that: Step 101, during heat treatment, the heating rate is 5°C / min, the temperature is 500-520°C, and the time is 4-5h.

4. The preparation of the selectively phosphated two-dimensional heterojunction photocatalyst according to claim 2, characterized in that: In step 102, during the annealing treatment, the temperature is 800-820°C and the time is 10-15 minutes.

5. The preparation of the selectively phosphated two-dimensional heterojunction photocatalyst according to claim 1, characterized in that: In step 1, the preparation steps of tungsten selenide nanosheets are as follows: tungsten selenide powder and sodium hydroxide nanosheets are added to an ethanol solution in a ratio of (1:1) to (1:2), stirred at room temperature, and then subjected to a hydrothermal reaction, and then naturally cooled to room temperature, and the precipitate is collected after centrifugal washing, and then dried to obtain tungsten selenide nanosheets.

6. The preparation of the selectively phosphated two-dimensional heterojunction photocatalyst according to claim 5, characterized in that: During the hydrothermal reaction, the temperature is 180~200℃ and the time is 10~12h.

7. The preparation of the selectively phosphated two-dimensional heterojunction photocatalyst according to claim 5, characterized in that: When drying, the temperature is 60~80℃ and the time is 10~18h.

8. The preparation of the selectively phosphated two-dimensional heterojunction photocatalyst according to claim 1, characterized in that: In step 2, the specific steps of the tungsten selenide-carbon nitride two-dimensional heterojunction catalyst are: Step 201, mixing, stirring and grinding tungsten selenide nanosheets and ultrathin graphite phase carbon nitride powder in a ratio of (1:50) to (15:50) to obtain a phosphated sample, and then putting the sample into a porcelain boat, and placing the porcelain boat at the lower air outlet of a tube furnace; Sodium hypophosphite is added into a porcelain boat, and the porcelain boat is placed at the upwind side of a tube furnace; wherein the ratio of sodium hypophosphite to the sample to be phosphated is (8:1) to (10:1); Step 202, connect the two ends of the tubular furnace quartz tube to the argon gas cylinder and the exhaust port, and exhaust in advance, then heat up to 200-220°C at 5°C / min, stop heating after phosphating for 2-4 hours, close the gas cylinder after the tubular furnace naturally cools to room temperature, open the tubular furnace, collect the powder sample, and grind it to obtain the phosphated tungsten selenide-carbon nitride two-dimensional heterojunction catalyst.

9. A product obtained by preparing the selectively phosphated two-dimensional heterojunction photocatalyst according to any one of claims 1 to 8.

10. Use of the photocatalyst as claimed in claim 9 in the field of hydrogen production.